Diagnóstico del consumo del portador energético electricidad en el bloque de extracción de petróleo 65, operado por el consorcio Petrosud Petroriva, durante el año 2015. Propuesta de un programa de mejora para la gestión de la energía eléctrica en base a la norma ISO 50001. - Cevallos Tapia, Edgar Fabián (2016)
The aim of this research is to develop an ISO 50001 standard compatible program, whose essentials contents are: Energy revision, Energetic Base Line, Indicators of Energy performance, targets and energetic goals; this program is designed for electric supply systems working in oil extracting blocks, in order to reach its management improvement. The oil extracting block 65, operated by “ConsorcioPetrosudPetroriva” was taken into account as an experimental plant during year 2015: at first, an energy flow review was carried out, basically by means of the “Total Energy Efficient Technology Management” tools.This characterization leads to the development of organizational measures requiring small and great investments, in order to take the best rational advantage of electricity as an energy carrier. Afterwards, a deep investigation about the electric energy use was performed, including elements related to the power variables, the energy quality and the identification of equipment and key-points common energetic statements. Different program phases, based on the energetic characterization and on the survey of the electric supply system were designed, in order to make the energy management compatible with the ISO 50001 standard and for the achievement of the best possible and most rational use of electricity in the considered plant